2016
DOI: 10.1038/ctg.2016.56
|View full text |Cite
|
Sign up to set email alerts
|

Weight and Body Composition Compartments do Not Predict Therapeutic Thiopurine Metabolite Levels in Inflammatory Bowel Disease

Abstract: OBJECTIVES:Thiopurine drugs are the most commonly used steroid-sparing therapies in moderate-to-severe inflammatory bowel disease (IBD). Their complex metabolism and their narrow therapeutic windows means that optimal dosing is difficult. However, weight-based dosing is the norm. Similar antimetabolites are dosed by body composition parameters. In IBD, treatment response and toxicity has been shown to correlate with thiopurine metabolite levels. We sought to determine whether weight or body composition paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In contrast, BMI was found to have no effect on rates of remission among patients with Crohn’s disease receiving ustekinumab maintenance therapy 17 . In addition, an analysis of the thiopurines azathioprine and mercaptopurine, which are dosed based on body weight, showed that therapeutic metabolite levels in patients with UC and Crohn’s disease were not related to weight or body composition compartments 18 . Together, these findings suggest that further research is required to better understand the impact of obesity on the efficacy of UC treatment and possible consequences of dosing regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, BMI was found to have no effect on rates of remission among patients with Crohn’s disease receiving ustekinumab maintenance therapy 17 . In addition, an analysis of the thiopurines azathioprine and mercaptopurine, which are dosed based on body weight, showed that therapeutic metabolite levels in patients with UC and Crohn’s disease were not related to weight or body composition compartments 18 . Together, these findings suggest that further research is required to better understand the impact of obesity on the efficacy of UC treatment and possible consequences of dosing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…17 In addition, an analysis of the thiopurines azathioprine and mercaptopurine, which are dosed based on body weight, showed that therapeutic metabolite levels in patients with UC and Crohn's disease were not related to weight or body composition compartments. 18 Together, these findings suggest that further research is required to better understand the impact of obesity on the efficacy of UC treatment and possible consequences of dosing regimens. Obesity is a known risk factor for reduced response to vaccines and for infection, 21,22 and in OCTAVE Induction 1 and 2 there was a numerically higher rate of serious infections and NMSC in the baseline BMI ≥30 subgroup treated with tofacitinib 10 mg b.d.…”
Section: Ta B L Ementioning
confidence: 99%
“…In this respect, there exists an association between the level of 6-thioguanine nucleotide (6-TGN), an azathioprine therapeutic metabolite, and clinical remission [127]. Holt et al [128] used cross-sectional CT imaging to investigate if body composition could provide more accurate means of achieving therapeutic levels of 6-TGN. They found no relationship between therapeutic levels of 6-TGN and subcutaneous or visceral fat, suggesting that the distribution of fat has little impact on thiopurine therapy.…”
Section: The Impact Of Adipose Tissue On Clinical Course and Theramentioning
confidence: 99%
“…The metabolite of immunosuppressants such as azathioprine was 6-thioguanine nucleotide (6-TGN) which are related to the effect of CD remission [ 31 ]. Holt et al demonstrated that VAT area and SAT area had no association the level of 6-TGN [ 32 ]. This may explain the reason why MFI was not related to the recurrence.…”
Section: Discussionmentioning
confidence: 99%